Do regeneration traits vary according to vegetation structure? A case study for savannas - Escobar, Diego F. E. [UNESP]; Silveira, Fernando A. O.; Morellato, Leonor Patrícia Cerdeira [UNESP] (Wiley-Blackwell, 2020)
Aim Regeneration traits are crucial for understanding patterns and processes in plant communities. However, regeneration traits are not reported much in community ecology, preventing a better assessment of trait-based community assembly. Here we assessed habitat-related regeneration traits by comparing species from open (grassland and shrubland) and closed (woodland) Brazilian savannas (cerrado). Location Our study site comprised two cerrado areas in southeastern Brazil that range from open to closed vegetation types, as examples of an ecological gradient of resources and environmental conditions. Methods We classified 82 species according to dormancy (non-dormant, physiological, physical, physiophysical, morphological, and morphophysiological dormancy), dispersal syndrome (autochory, anemochory, exozoochory, endozoochory), and dispersal season (rainy, dry, rainy-to-dry and dry-to-rainy transitions). We determined seed mass, germination percentage, mean germination time and coefficient of variation of germination time in conditions of optimal temperatures. Principal coordinates Analysis (PCoA) was used to explore the relationships between regeneration traits and vegetation types. Results The two main axes of the PCoA explained 38% of the total variance. The first axis was related to germination traits (germination percentage, mean gemination time, and coefficient of variation of gemination time) and separated dormant from non-dormant species, whereas the second axis was related to seed mass, growth form, and dispersal syndromes which sharply separated open- and closed-savanna species. Unexpectedly, seed germination and dormancy traits did not differ among open- and closed-savanna species. Conclusions Seasonality is a strong filter for both germination and seedling establishment that shapes germination strategies regardless of vegetation type. The dominant strategy was dispersal of non-dormant seeds in the rainy season, while the least common strategy was dispersal of dormant seeds during the rainy-to-dry season transition. Habitat-related germination strategies were related to growth form and seed mass, improving our understanding of community assembly in species-rich Brazilian savannas.
Keywords: cerrado; environmental heterogeneity; seed dormancy; seed traits; trait-based community assembly